Consumers’ Costly Responses to Product-Harm Crises - Ferrer, Rosa; Perrone, Helena (Management Science, 2023)
This paper exploits a major food safety crisis to estimate a full demand model for the unsafe product and its substitutes, recovering consumers’ preference parameters for different product characteristics. Counterfactual exercises quantify the relevance of different mechanisms driving consumers’ responses, such as changes in safety perceptions, idiosyncratic taste, product characteristics, and price. We find that consumers’ reactions are limited by their preferences for the product’s observable and unobservable characteristics. Because of the costs associated with switching from the affected product, the decline in demand following a product-harm crisis tends to understate the true weight of such events in consumers’ utility. We find that unobservable taste is a crucial driver of consumers’ responses. Our counterfactual exercises illustrate that the demand would have declined further if consumers had had access to a closer substitute. For an accurate assessment of product-harm crises, managerial strategies should therefore account for how different demand drivers bind consumers’ substitution patterns. This paper was accepted by Matthew Shum, marketing. Funding: This work was supported by the Ministerio de Ciencia e Innovación [Grants ECO2008-01116 and ECO2010-15052], the Ministerio de Economía y Competitividad [Grant ECO2013-43011-P], and the Deutsche Forschungsgemeinschaft [Grant CRC TR 224]. R. Ferrer received support from [Grant ECO2016-76998-P], and the Severo Ochoa Programme for Centers of Excellence in R&D [SEV-2015-0563].